The Role of Family Support in Improving Pregnant Women's Compliance with Antenatal Care in the Totoli Public Health Center Area - Erviana Erviana; Muhammad Taufik Page; Muhammad Amin; Tepi Tepi (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Antenatal Care (ANC) is an essential health service for pregnant women aimed at monitoring both maternal and fetal conditions regularly, in accordance with standard healthcare protocols. Compliance with ANC schedules is influenced by various factors, one of which is family support. This study aimed to examine the relationship between family support and pregnant women's compliance with ANC visits in the working area of Totoli Primary Health Center. A quantitative research design was employed, using purposive sampling and data collection through structured questionnaires. The study involved 93 respondents who met the inclusion criteria: pregnant women residing in the Totoli Health Center service area, currently undergoing antenatal care, and in their third trimester of pregnancy. Data were analyzed using the Gamma correlation test. The results revealed that 44.1% of the respondents received low family support, and 62.4% showed low compliance with ANC visits. Statistical analysis indicated a significant relationship between family support and ANC compliance, with a p-value of 0.000. In conclusion, the study demonstrated a significant association between family support and pregnant women's compliance with Antenatal Care.